An assessment on the effectiveness of the SADC protocol in combating illicit drug trafficking: a comparative study of Zimbabwe and South Africa - Munyonga, M. (BUSE, 2023)
The researcher noted that there is an increase in drug flow and drug uptake in the region prompting the need to analyse the effectiveness of the SADC protocol on combating drug trafficking between Zimbabwe and South Africa. Consequently, research objectives are: 1) To assess the effectiveness of the destruction of seized drugs as a tool toward combating drug trafficking. 2) To evaluate the effectiveness of maximum custodial sentence as both a deterrent and punishment in combating drug trafficking. 3) To analyse the effectiveness of mutual assistance between states in combating drug trafficking. 4) To examine the effectiveness of tracing, freezing and seizure, confiscation and forfeiture of proceeds in combating drug trafficking. 5) To evaluate the effectiveness of rehabilitation on offenders in drug trafficking. The population size is 60 inclusive of managerial and non-managerial staff. The sample size is 30. Sampling methods used were the convenience and stratified sampling. A descriptive approach was adopted whilst the research instruments which included; questionnaires, interviews and documentary sources were used. Questionnaires were self administered and validity was enhanced through a pilot test of questionnaires before final distribution. Ethical consideration was maintained through privacy confidentiality. Obtained data was analysed, interpreted and presented on graphs, tables and pie chart. Findings were that there is mutual cooperation between Zimbabwe and South Africa in combating drug trafficking through effecting of the SADC protocol. Recommendations included the need by the two nation states to remunerate workers, sharpen the law enforcement agencies through training and development and capacitate institutions engaged in combating of illicit drugs.